Open-label trials for CGRP-targeted drugs in migraine prevention: A narrative review. (February 2023) - Raffaelli, Bianca; De Icco, Roberto; Corrado, Michele; Terhart, Maria; Ailani, Jessica
Background: Calcitonin gene-related peptide-targeted drugs have proven safe and effective for migraine prevention in large randomized-controlled, double-blind trials with an average duration of six months. Open-label studies may provide additional information on the long-term safety and efficacy of these substances. Methods: We searched PubMed for open-label trials with calcitonin gene-related peptide(-receptor) monoclonal antibodies and calcitonin gene-related peptide-receptor antagonists. We summarized and critically analyzed the literature in a narrative way. Results: Overall, 13 open-label trials were included in this review (n = 4 for erenumab, n = 4 for galcanezumab, n = 3 for fremanezumab, n = 1 for eptinezumab, n = 1 for atogepant). Open-label trial duration ranged between 12 and 264 weeks. No safety concerns emerged, and the adverse events profile was similar to the double-blind study phase. Discontinuation rates were generally low with >75% of patients remaining in the trials after one year. Efficacy data showed a sustained reduction of migraine frequency throughout the trials, along with a lasting improvement in quality of life. Conclusions: The open-label study program for calcitonin gene-related peptide-targeted migraine preventives confirms the favorable safety and efficacy profile of these drugs over time. Treatment adherence appears higher than with previous unspecific migraine preventives. Real-world data and post-marketing surveillance studies may corroborate and complement open-label results.